An Econometric Analysis of the Relationship between Changes in Government Bonds, Exchange Rate and Inflation Dynamics in South Africa - A, Sanusi K; F, Meyer D (Journal of Economics and Behavioral Studies, 2018)
The study examined the dynamic interaction between government bonds, exchange rate and inflation in South Africa. The study follows a quantitative research method, using monthly time series data from 2007 to 2017 within the framework of a Vector Autoregressive Analysis (VAR). Evidence from the empirical analysis shows that government bond accounts for significant variation in the exchange rate and inflation rate within the study period. The causality test also suggests the presence of uni-directional causal relationships from government bonds to exchange rate, and also to the inflation rate. The principal conclusion that emanates from the empirical analysis is that government bonds are an important policy instrument in the management of the exchange rate and the inflation rate in South Africa. The study recommends that the South African Reserve Bank is a coordinator of government bond and should carry out an in-depth analysis of the economic conditions before issuing the government bonds, taking into account its impeding effects on the exchange rate and inflation rate and many other macroeconomic variables.